(untitled) (Journal of Digital System Development, 2023)
The Nanny Care mobile app has accomplished a significant mobile development application targeted at post-natal women. This app aims to solve the challenges post-natal women face in accessing reliable and safe confinement care services. Additionally, it creates a golden opportunity for the confinement ladies to promote and provide their confinement services to the targeted customers. On the other hand, this study follows the Extreme Programming (XP) methodology, which focuses on iterative development and continuous customer feedback. Specifically, this app allows post-natal women (users) to register and log in, view confinement ladies’ profiles, book services, view past bookings, and rate confinement ladies. Based on the usability evaluation of the app, it has shown that users found it helpful, easy to use and efficient. The users’ feedback highlights the app’s strengths and suggests areas for improvement, such as additional features and better error handling. Overall, this Nanny Care mobile app has the potential to enhance the post-natal women’s confinement experience, empowering confinement ladies to offer their services and providing a reliable platform for accessing and providing quality care.